2017
DOI: 10.1371/journal.pone.0168435
|View full text |Cite
|
Sign up to set email alerts
|

L-Type Calcium Channel Inhibition Contributes to the Proarrhythmic Effects of Aconitine in Human Cardiomyocytes

Abstract: Aconitine (ACO) is well-known for causing lethal ventricular tachyarrhythmias. While cardiac Na+ channel opening during repolarization has long been documented in animal cardiac myocytes, the cellular effects and mechanism of ACO in human remain unexplored. This study aimed to assess the proarrhythmic effects of ACO in human induced pluripotent stem cell-derived cardiomyocytes (hiPSC-CMs). ACO concentration-dependently (0.3 ~ 3.0 μM) shortened the action potentials (AP) durations (APD) in ventricular-like hiPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…Furthermore, the results suggested that ACO-induced cardiomyocyte death is mediated, at least in part, by inducing apoptosis. Overall, these results are in agreement with those of previous studies from cellular and human biopsy studies demonstrating ACO-induced cardiotoxicity ( 7 , 9 , 22 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, the results suggested that ACO-induced cardiomyocyte death is mediated, at least in part, by inducing apoptosis. Overall, these results are in agreement with those of previous studies from cellular and human biopsy studies demonstrating ACO-induced cardiotoxicity ( 7 , 9 , 22 ).…”
Section: Discussionsupporting
confidence: 92%
“…Studies have reported that ACO is capable of inducing VT and VF by opening the Na + channels of isolated cardiac myocytes from mice, rats, guinea pigs and rabbits ( 21 ). In addition, ACO-induced LTCC inhibition has been reported ( 5 , 22 ). In the present study, the RTCA Cardio system was applied, which is able to monitor the contractility of cardiomyocyte in real-time, to evaluate the arrhythmogenic effects of ACO in hiPSC-CMs.…”
Section: Discussionmentioning
confidence: 98%
“…The increase in intracellular Na + favors an increase in intracellular Ca 2+ through the activation of the Ca 2+ /Na + bidirectional exchanger and the release of intracellular Ca 2+ stored in the sarcoplasmic reticulum [18,25,26]. Aconitine has also been shown to block the potassium channels responsible for rapid and ultra-rapid delayed rectifier currents, which can result in further prolongation of the action potential [15,25,27]. The effects on calcium and potassium develop delayed afterdepolarization during the refractory period.…”
Section: Discussionmentioning
confidence: 99%
“…Higher concentrations of aconitine suppress action potential transmission by continuous opening of the Na + channel, which reduces the release of acetylcholine at the axonal end terminus and the vagotonic effects at the myocardium [18,25]. The bradycardia and hypotensive manifestations can be explained by activation of the ventromedial nucleus of the hypothalamus associated with depression of the circulatory system and inhibition of L-type calcium channel currents that serve as a major driver of pacemaker monocytes [18,21,25,26,27]. These complex electrophysiological mechanisms generate self-excitatory abnormal microcircuits within the cardiac and nervous systems, which can trigger cardiovascular features such as arrhythmia, conduction blocks, bradycardia and asystole [18,25].…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, aconitine could also shorten action potential duration, reduce L-type calcium currents, thereby contributing to the proarrhythmic effects in human-induced pluripotent stem cellderived cardiomyocytes. The effects of aconitinecaused arrhythmia and underlying mechanisms were further studied in human cardiomyocytes model [67]. In addition, it is noteworthy that the Na þ -Ca 2þ exchange (NCX) system plays a vital role in regulating cardiac contractility and electrical activity in different animal modes.…”
Section: Toxic Mechanisms Of Aconitine In Cardiac Systemmentioning
confidence: 99%